MPox Skin Lesions - Robert Sinto; Alvin Johan; Hanny Nilasari; Evy Yunihastuti; Erni J Nelwan (Acta Medica Indonesiana)
Mpox is caused by the Monkeypox virus, which belongs to the Orthopoxvirus genus and Poxviridae family. The Monkeypox virus was first identified as a cause of disease in humans in the 1970s in the Democratic Republic of the Congo. Mpox was considered endemic in several African countries. A global outbreak of Mpox was first recognized in Europe in May 2022 and was declared a public health emergency of international concern on July 23, 2022. The first reported Mpox case in Indonesia was in October 2022 which was identified as an imported case, there were no new confirmed Mpox cases until 13 October 2023. Since then there were 72 cases of confirmed Mpox cases in Indonesia by the end of 2023, distributed across 6 provinces, mostly in the Java island.